THE UNIVERSAL PERIODIC REVIEW: A DEVICE FOR BUILDING UP COOPERATION WITH HUMAN RIGHTS MECHANISMS IN BRAZIL AND MIGRATION PROTECTION - DOI 10.5935/2448-0517.20200043 - Duarte, Fernanda; Iorio Filho, Rafael Mario (Juris Poiesis - Qualis A3, 2020)
This presentation is part of a research project developed within the scope of the international academic cooperation program between Estácio de Sá University, the Fluminense Federal University and Birmingham City University, under the Erasmus + program, electing as its motive theme the Universal Periodical Review- UPR, adopted by the Human Rights Council of the United Nations. One of the objectives of this UPR mechanism is to assure that human rights obligations and commitments are fulfilled by the States in order to promote the universality and indivisibility of civil, political, economic, social, and cultural rights as well as the right to development. In this sense, one of the axes of relevance for improvement of the human rights situation in every country with significant consequences for people all around the globe focuses on building up a legal framework (with international legal sources or roots) that could be articulated locally as a shield for those who (legally bound to the State) find themselves in situations of human rights violations. This shield makes the State internationally accountable for violating its duty to comply with international norms. Even though this spectrum of legal normativity is not enough to assure human rights full effectiveness in all the levels and complexities of human life and existence, it brings the symbolic weight of the idea of the rule of law. In this opportunity, we intend to present the legal framework for the promotion and protection of human rights in Brazil, taking into account BrazilÂ´s constitutional order and its relation with international legal instruments. Then considering BrazilÂ´s performance within the UPR 3rd Cycle, 2017, 27th Session, we will discuss Brazil"s compliance with this international environment of instruments for protecting human rights taking the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families recommendation as an example to be studied.